Psychoanalytic inpatient psychotherapy of depression – Two naturalistic samples throughout the course of a decade. Issue 4 (2nd October 2017) - Fizke, Ella; Mueller, Axel; Huber, Dorothea
Abstract: Background: While the general effectiveness of psychodynamic inpatient psychotherapy has been established, very few studies have specifically investigated the effectiveness of psychodynamic inpatient treatment of depression, though depressed patients represent the largest group of inpatients. Method : This study investigated two naturalistic samples of depressed patients regarding treatment outcome as well as clinical and treatment characteristics. Patients were treated in a psychoanalytical psychosomatic hospital unit. Data was collected from 2000 to 2002 (N=234) and from 2008 to 2010 (N=514). Data was acquired at admission and discharge. Results: The findings reveal high pre-post effect sizes for symptom reduction (SCL-90-R), general functioning (GAF) and medium changes of interpersonal problems (IIP). The improvement on the IIP was significantly higher for patients with comorbid personality disorder. Based on therapist ratings, the sample treated from 2008-2010 showed higher levels of impairment on several levels: chronic, complex, functional (GAF) and structural (OPD). Conclusion: Findings indicate that patients show substantial short-term benefit following psychoanalytic inpatient psychotherapy, as practiced under naturalistic conditions. Open questions remain regarding the long-term nature of these benefits and the possible influence of placebo-effects.